Brief Report: Sex Differences in Outcomes for Individuals Presenting for Third-Line Antiretroviral Therapy. (1st June 2020) - Godfrey, Catherine; Hughes, Michael D.; Ritz, Justin; Coelho, Lara; Gross, Robert; Salata, Robert; Mngqibisa, Rosie; Wallis, Carole L.; Mumbi, Makanga. E.; Matoga, Mitch; Poongulali, Selvamuthu; Van Schalkwyk, Marije; et al.
Abstract : Background: Sex differences in studies of antiretroviral (ART) drug exposure and treatment outcomes support the hypothesis that some ART combinations may not be well tolerated in women. We evaluated disparities in outcomes between men and women participating in ACTG A5288, an interventional strategy trial for individuals failing a protease inhibitor–based second-line ART regimen in low- and middle-income countries. Methods: Participants were assigned to one of 4 cohorts (A-D) based on resistance profiles and ART history. Cohort A had no lopinavir/ritonavir (LPV/r) resistance and stayed on their second-line regimen, and cohorts B, C, and D had increasing resistance and accessed novel ART regimens. In this secondary analysis, we evaluated sex differences in the primary endpoint, HIV-1 RNA ⩽200 copies/mL at week 48; confirmed virologic failure ≥1000 copies/mL (VF); and clinical outcomes and adverse events (intent-to-treat). Results: Women made up 258/545 (47%) of the study population. More women than men were assigned to cohort A. Median follow-up was 72 weeks. Fewer women than men had HIV-1 RNA ⩽200 copies/mL at week 48: 39% vs. 49% in cohort A and 83% vs. 89% in cohorts B, C, and D combined. More women experienced VF, grade ≥3 signs and symptoms, but similar grade ≥3 diagnoses or laboratory abnormalities. Conclusions: More women than men entered the study with a resistance profile suggesting that their second-line regimen could have been effective in maintaining virologic suppression. The more frequent occurrence of grade ≥3 signs and symptoms in women suggests that tolerability issues were under recognized in women on protease inhibitor–based therapy.